Aloe vera mitigates dextran sulfate sodium-induced rat ulcerative colitis by potentiating colon mucus barrier. (28th October 2021) - Shi, Gaofeng; Jiang, Hui; Feng, Jianrong; Zheng, Xian; Zhang, Dongjian; Jiang, Cuihua; Zhang, Jian
Abstract: Ethnopharmacological relevance: Aloe vera (L.) Burm. f. ( Aloe vera ) is a medicinal herb that used in Traditional Chinese Medicine (TCM) practice for the treatment of gastrointestinal diseases such as constipation and colitis. Recent studies also reported its beneficial effect in mitigating ulcerative colitis (UC). Nevertheless, the underlying mechanisms of Aloe vera against UC remain largely unknown. Aim of the study: This study aimed to explore a relation between the therapeutical effects of Aloe vera in UC and colonic mucus secretion, and further investigate the underlying pathways through which Aloe vera regulates colon mucus as well as preliminarily studied the main active constitute of Aloe vera to alleviate UC. Materials and methods: UPLC-MS/MS were employed to analyze the Aloe vera extract. The rat models of UC were induced by free subjected to fresh 3% dextran sulfate sodium (DSS) solution for 8 days and then accessed to tap water for 2 days. Aloe vera extract (18 mg/kg and 72 mg/kg) or 5-ASA (400 mg/kg) was administered orally from day 1–10. At the end of experiment, rats were sacrificed and the colon tissues were harvested for analysis. UC symptoms was evaluated by disease activity index (DAI), colon length and H&E staining. The Alcian blue stain were determined colon mucus layer. Myeloperoxidase (MPO) activity, mucin and inflammatory cytokines in colon tissues were determined by ELISA. The expression of related proteins on PI3K/AKT and PKC/ERK signaling pathway was analyzed by Western blot. We then evaluated the effects of three main components of Aloe vera (Aloe-emodin, aloin A and B) on mucin secretion and cytokine expression in vitro by ELISA. Results: Oral supplement with Aloe vera extract resulted in a significantly decreased DSS-induced UC symptoms, including decreased DAI, prevention of the colon length shortening, and alleviation of the pathological changes occurring in colon. The expression of colonic pro-inflammatory mediators, including IL-6, IL-1β and TNF-α were suppressed, yet the expression of IL-10 was up-regulated by Aloe vera treatment. Moreover, Aloe vera significantly up-regulated the expressions of mucin proteins (e.g., MUC2 and MUC5AC) and increased the thickness of mucus layer in the colon. Further, we revealed that Aloe vera significantly upregulated p-PKC and p-ERK expression and downregulated p-PI3K and p-AKT expression. Finally, we discovered that treat with aloin A markedly decreased IL-6 levels and increased MUC2 expression in LPS-stimulated LS174T cell. Conclusion: These results support that Aloe vera improved UC by enhancing colon mucus barrier functions in addition to reducing inflammation. Moreover, aloin A might be a main active components of Aloe vera to ameliorate UC. Graphical abstract: Image 1